Meningkatkan Aktivitas, Motivasi Dan Hasil Belajar Menggunakan Model Pbl, Stad dan Nht Di Sekolah Dasar - M. Rifki Fauzan; Asrani . (CV. ITTC INDONESIA, 2024)
The problem with this study is that students tend to be passive and do not want to ask questions during IPAS learning, and when the teacher asks them questions, students only respond with answers that are already in the book. The researchers attempted to provide a solution to these issues as a follow-up by employing a combination of Problem Based Learning, Student Teams Achievement Division, and Numbered Head Together learning models. This study employs qualitative research as its method, and class action research is used in this type of study. The kinds of information introduced in this study are subjective information and quantitative information. Subjective information as information on educator exercises and understudy exercises in the instructing and growing experience exercises, through perceptions with perception sheets. quantitative data in the form of the learning outcomes of the students that are obtained from written tests at the conclusion of each meeting. This examination was led at SDN Antasan Besar 1 in the even semester of class IV in the 2023/2024 scholastic year. At each of the four meetings, the activities of teachers, students, student learning motivation, and learning outcomes increased with the categories